The effect of green technology innovation on air pollution from a quantity–quality perspective in China’s large river basins - Guangzhi Qi; Zhibao Wang; Chao Teng; Jinli Zhao; Yu Cheng; Chengxin Wang (Scientific Reports)
Abstract Green technology innovation (GTI) plays a crucial role in promoting regional sustainable development, yet its mechanisms for mitigating air pollution remain insufficiently explored. This study investigates the spatio-temporal dynamics and spatial correlations of GTI and air pollution across China’s major river basins, with a particular focus on differentiating the roles of GTI quantity and quality. Using the extended STIRPAT and spatial Durbin models, we examine nonlinear relationships, basin-specific heterogeneity, and spatial spillover effects. Results show that GTI quantity followed a core-periphery diffusion pattern, while GTI quality exhibited fluctuating trends with recent stabilization. An inverted “U” shaped relationship was observed between both GTI dimensions and PM2.5 and PM10 concentrations, locally and in neighboring areas. Notably, inflection points for GTI quantity lagged behind those for quality, and post-inflection pollution-reduction effects differed across basins—being stronger in the Yangtze River Basin for PM2.5, but in the Yellow River Basin for PM10. These findings highlight the differentiated mechanisms through which GTI affects air quality, offering valuable insights for targeted innovation policies and regional coordination in sustainable governance.